Optimalisasi Pemanfaatan Sistem Informasi Desa dalam Pendataan dan Pemantauan Penduduk pada Masa Pandemi Covid-19 - M. Husni Tamrin; Sri Umiyati; Lunariana Lubis; Wildan Taufik Raharja (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2022)
This community service aims to assist the village government of Ambeng-ambeng Watangrejo in Duduksampeyan Sub-District, Gresik Regency in registering and monitoring immigrants and conducting independent home isolation as a result of implementing the Widespread Social Restrictions Policy (PSBB) during the COVID-19 pandemic. The village government and the 19th level COVID task force are facing hurdles in collecting data and monitoring the isolated population. So there is a need for an online village information system that can record and monitor the population. The community is served through socialization methods and by assisting village officials and the Covid-19 task force in implementing the village information system. A community service outcome is a village information system that the village government can use to provide services to the community.